To the History of M. V. Lomonosovâ€™s â€œRussian Grammarâ€: Chronology, Versions, Collaborators - Kareva, Natalia V.; Pivovarov, Evgeny G. (SlovÄ›ne = Ð¡Ð»Ð¾Ð²Ñ£Ð½Ðµ. International Journal of Slavic Studies, 2019)
The paper is an attempt to review and clarify data concerning Mikhail Lomonosovâ€™s grammar studies and especially the history of his famous â€œRussian Grammarâ€. The authors lay out the timeline of its creation and publication. They describe the main steps on its way from the author to the reader and discuss evidence of its manuscript versions. Scholars know of at least four handwritten copies, none of which survive or have been identified. Only a few related drafts known as â€œManuscript 112â€ or â€œMaterials to the Russian Grammarâ€ are available in the archive of the Russian Academy of Sciences (published in volume 7 of his Lomonosov's Complete Works). The article examines two parts of this manuscript which were apparently written not by Lomonosov: 1) lists of words and drafts of sections devoted to different parts of speech; 2) comments on some paragraphs of the â€œRussian Grammarâ€. Comparison of handwriting samples shows that the first part was not, as previously suggested, written by Lomonosovâ€™s long-time assistant and copyist Ivan Barkov, while the second part was probably written by Lomonosov's classmate and fellow worker at the Academy Aleksey Barsov.Â DOI:10.31168/2305-6754.2019.8.2.7 Ð’ ÑÑ‚Ð°Ñ‚ÑŒÐµ ÑÐ´ÐµÐ»Ð°Ð½Ð° Ð¿Ð¾Ð¿Ñ‹Ñ‚ÐºÐ° Ð¾Ð±Ð¾Ð±Ñ‰Ð¸Ñ‚ÑŒ Ð¸ ÑƒÑ‚Ð¾Ñ‡Ð½Ð¸Ñ‚ÑŒ Ð¸Ð½Ñ„Ð¾Ñ€Ð¼Ð°Ñ†Ð¸ÑŽ Ð¾Ð± Ð¸Ð·Ñ‹ÑÐºÐ°Ð½Ð¸ÑÑ… Ðœ.Â Ð’.Â Ð›Ð¾Ð¼Ð¾Ð½Ð¾ÑÐ¾Ð²Ð° Ð² Ð¾Ð±Ð»Ð°ÑÑ‚Ð¸ Ð³Ñ€Ð°Ð¼Ð¼Ð°Ñ‚Ð¸ÐºÐ¸ Ñ€ÑƒÑÑÐºÐ¾Ð³Ð¾ ÑÐ·Ñ‹ÐºÐ° Ð¸ ÑÐ¾Ñ‡Ð¸Ð½ÐµÐ½Ð¸Ñ Ð¸Ð¼ Ð·Ð½Ð°Ð¼ÐµÐ½Ð¸Ñ‚Ð¾Ð¹ Â«Ð Ð¾ÑÑÐ¸Ð¹ÑÐºÐ¾Ð¹ Ð³Ñ€Ð°Ð¼Ð¼Ð°Ñ‚Ð¸ÐºÐ¸Â». ÐÐ²Ñ‚Ð¾Ñ€Ñ‹ Ð²Ð¾ÑÑÑ‚Ð°Ð½Ð°Ð²Ð»Ð¸Ð²Ð°ÑŽÑ‚ Ñ…Ñ€Ð¾Ð½Ð¾Ð»Ð¾Ð³Ð¸ÑŽ Ð½Ð°Ð¿Ð¸ÑÐ°Ð½Ð¸Ñ ÑÑ‚Ð¾Ð³Ð¾ Ñ‚ÐµÐºÑÑ‚Ð° Ð¸ Ð¿Ð¾ÑÐ»ÐµÐ´ÑƒÑŽÑ‰ÐµÐ¹ Ñ€Ð°Ð±Ð¾Ñ‚Ñ‹ Ð½Ð°Ð´ Ð½Ð¸Ð¼, Ñ€Ð°ÑÑÐ¼Ð°Ñ‚Ñ€Ð¸Ð²Ð°ÑŽÑ‚ ÑÐ¾Ð±Ñ‹Ñ‚Ð¸Ñ, Ð¿Ñ€ÐµÐ´ÑˆÐµÑÑ‚Ð²Ð¾Ð²Ð°Ð²ÑˆÐ¸Ðµ Ð²Ñ‹Ñ…Ð¾Ð´Ñƒ ÐºÐ½Ð¸Ð³Ð¸ Ð² ÑÐ²ÐµÑ‚, Ð¾Ð±ÑÑƒÐ¶Ð´Ð°ÑŽÑ‚ ÐµÐµ Ñ€ÐµÐ´Ð°ÐºÑ†Ð¸Ð¸, ÑƒÐ¿Ð¾Ð¼Ð¸Ð½Ð°Ð²ÑˆÐ¸ÐµÑÑ Ð² Ñ€Ð°Ð±Ð¾Ñ‚Ð°Ñ… Ð¿Ñ€ÐµÐ´ÑˆÐµÑÑ‚Ð²ÐµÐ½Ð½Ð¸ÐºÐ¾Ð². Ð’ Ð½Ð°ÑÑ‚Ð¾ÑÑ‰ÐµÐµ Ð²Ñ€ÐµÐ¼Ñ Ð¸ÑÑÐ»ÐµÐ´Ð¾Ð²Ð°Ñ‚ÐµÐ»Ð¸ Ð·Ð½Ð°ÑŽÑ‚ Ð¾ Ð¿Ð¾ Ð¼ÐµÐ½ÑŒÑˆÐµÐ¹ Ð¼ÐµÑ€Ðµ Ñ‡ÐµÑ‚Ñ‹Ñ€ÐµÑ… Ñ€ÑƒÐºÐ¾Ð¿Ð¸ÑÐ½Ñ‹Ñ… ...